Aspek Hukum Subyek Pajak Bentuk Usaha Tetap Menurut Hukum Positif di Indonesia - Paulus Aluk Fajar Dwi Santo (Bina Nusantara University, 2010)
PE (Permanent Establishment) is an international tax terminology which is a consequence of the operations of the base/fixed sites in the treaty partner country, after fulfilling certain conditions stipulated in the Tax Treaty or the Act, such as: types of business activities conducted in the country treaty partner, source of income and the term (